Pengaruh Financial Literacy dan Financial Attitude terhadap Financial Management Behavior Self efficacy sebagai variabel mediasi Pada UMKM Kota Pekanbaru - Wahyuningsih, Eny; Sastraningsih, Ellyan; Suryadi, Nanda (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to determine the effect of Financial Literacy and Financial Attitude on Financial Management Behaviour Self Efficay as a Mediating Variable.  The data collection method in this study uses primary data obtained from the results of filling out questionnaires to 100 respondents in Pekanbaru City MSME players and secondary data obtained from literature books and journals related to this research.  The data analysis method used is descriptive analysis, and the data processing technique uses SEM Smart Pls.  The results of this study indicate that Financial Literacy, Financial Attitude and Financial Self Efficacy directly have a positive and significant effect on Financial Management Behaviour. While indirectly Self Efficacy mediates Financial Literacy has an effect on Financial Management Behavior and Self Efficacy mediates Financial Attitude has an effect on Financial Management Behavior, the author's suggestion for further research is that the results of this study can be a reference for further similar research by developing other variables that affect financial management behavior that researchers have not been able to include in this study.